2004
DOI: 10.1063/1.1785284
|View full text |Cite
|
Sign up to set email alerts
|

Electron accumulation layer at the Cs-covered GaN(0001) n-type surface

Abstract: We report on the observation of photoemission from the Cs∕GaN(0001) n-type interface by excitation of visible light in the transparency region of GaN. Under Cs adsorption, sharp decrease in photoemission threshold up to 1.3eV at 0.5 monolayer of Cs is found and shown to be due to formation of a charge accumulation layer in the near-interface region. An interesting phenomenon is revealed, namely, the appearance of an oscillation structure in spectra of photoyield. A model conception taking into account both the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 14 publications
0
8
1
Order By: Relevance
“…However, the authors of Ref [10] [11] [12] do not report on the exact value of QE, but only report that the maximal QE of the Cs/n-GaN system is comparable and even exceeds the QE for highly-efficient source of electron GaAs photo-cathodes, which can reach 50% [14]. Therefore, we assume that the QE for the Cs/n-GaN system is also not less than 50% at room temperature for photon energy 3.1 eV (5) shows that in the conventional Fowler regime for a temperature range from 300 to 500 K the QE value increases by only on 0.7%.…”
Section: Temperature Dependent Photoemission From Accumulation Layersmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the authors of Ref [10] [11] [12] do not report on the exact value of QE, but only report that the maximal QE of the Cs/n-GaN system is comparable and even exceeds the QE for highly-efficient source of electron GaAs photo-cathodes, which can reach 50% [14]. Therefore, we assume that the QE for the Cs/n-GaN system is also not less than 50% at room temperature for photon energy 3.1 eV (5) shows that in the conventional Fowler regime for a temperature range from 300 to 500 K the QE value increases by only on 0.7%.…”
Section: Temperature Dependent Photoemission From Accumulation Layersmentioning
confidence: 99%
“…Therefore, the exact value of the Fermi and vacuum energy levels is a crucial parameter in the calculation of the threshold energy for photoemission. For a clean n-GaN (0001) surface the reported room temperature work function Φ and electron affinity χ are 3.9 and 3.35 eV respectively [10]. In this case the Fermi energy is ( ) ( ) 300 0.55 eV,…”
Section: Room Temperature Threshold Energy Of Photoemission For N-ganmentioning
confidence: 99%
See 1 more Smart Citation
“…The method is based on the separation of the bulk and surface photoemission, as well as on the effect of the near-thresh- We have earlier revealed that the electron properties of the n -GaN(0001) surface change radically during the process of the formation of ultrathin Cs/ n -GaN(0001) and Ba/ n -GaN(0001) interfaces at the initial adsorption stage at the submonolayer Cs and Ba coatings. In this case, the main effect is the appearance of a 2D electron channel, which is a charge accumulation layer (CAL) on the GaN surface [14]. We recorded for the first time this phenomenon in the wide-bandgap semiconductors.…”
mentioning
confidence: 94%
“…The surface properties of polar and nonpolar GaN surfaces as well as adsorption and interaction processes have been studied to a relatively broad extent . However, there are still unanswered or only recently addressed scientific questions related to surface adsorption kinetics and how they can be used for generation of novel functionality or for the manipulation of the electronic properties. , As an example, the adsorption of alkali and alkaline earth metal atoms at polar GaN surfaces has also been studied for the cases of cesium (Cs) and barium (Ba). For both alkali metals, a deposition time-dependent modification of the surface electronic properties was observed, with a strong reduction of the work function induced by formation of an adatom-induced surface dipole, which lowers the surface barrier for electron emission. At the same time, the adatoms induce changes in surface band bending and surface/adatom states within the fundamental band gap of GaN.…”
Section: Introductionmentioning
confidence: 99%